Answer:[tex]a = \frac{F}{m}[/tex]
[tex]v = \frac{m}{d}[/tex]
[tex]t = \frac{A - P}{Pr}[/tex]
[tex]h = \frac{2A}{a + b}[/tex]
[tex]W = \frac{P - 2L}{2}[/tex]
[tex]y = 2m - x[/tex]
[tex]y = -1.5x + 4[/tex]
[tex]t = \frac{v - u}{a}[/tex]
Step-by-step explanation:
[tex]F = ma[/tex]
[tex]\frac{F}{m} = \frac{ma}{m}[/tex]
[tex]\frac{F}{m} = a[/tex]
[tex]d = \frac{m}{v}[/tex]
[tex]vd = m[/tex]
[tex]\frac{vd}{d} = \frac{m}{d}[/tex]
[tex]v = \frac{m}{d}[/tex]
[tex]A = P + Prt[/tex]
[tex]A - P = Prt[/tex]
[tex]\frac{A - P}{Pr} = \frac{Prt}{Pr}[/tex]
[tex]\frac{A - P}{Pr} = t[/tex]
[tex]A = \frac{1}{2}h(a + b)[/tex]
[tex]2A = h(a + b)[/tex]
[tex]\frac{2A}{a + b} = \frac{h(a + b)}{a + b}[/tex]
[tex]\frac{2A}{a + b} = h[/tex]
[tex]P = 2(L + W)[/tex]
[tex]P = 2(L) + 2(W)[/tex]
[tex]P = 2L + 2W[/tex]
[tex]P - 2L = 2W[/tex]
[tex]\frac{P - 2L}{2} = \frac{2W}{2}[/tex]
[tex]\frac{P - 2L}{2} = W[/tex]
[tex]m = \frac{x + y}{2}\\2m = x + y\\2m - x = y[/tex]
[tex]3x + 2y = 8\\2y = -3x + 8\\\frac{2y}{2} = \frac{-3x + 8}{2}\\y = -1.5x + 4[/tex]
[tex]a = \frac{v - u}{t}\\at = v - u\\\frac{at}{a} = \frac{v - u}{a}\\t = \frac{v - u}{a}[/tex]